A HUMAN DIMENSION MODEL FOR THE URBAN VERTICAL HOUSING SUSTAINABILITY THROUGH INDOOR AIR QUALITY - Nurwidyaningrum, Dyah; Kusnoputranto, Haryoto; Moersidik, Setyo S.; -, Masfuri (PLANNING MALAYSIA, 2022)
In urban vertical housing in Jakarta, air conditioning (AC) is mainly used to create comfort in units and spare residents from hazardous outdoor pollution. Residents in urban vertical housing, who have come from the surrounding multi-ethnic area, live in dense conditions. This situation inflicts conflicts of interest that affect indoor air quality (IAQ). This research develops a human dimension model for promoting indoor air quality in dense urban housing using the concept of sustainability, which is an environmental science approach. This study aims to conceptualize the effect of the human dimension in IAQ planning. The method is partial least squares-self equation modelling (PLS-SEM) analysis. The indicator variables of the human dimension related to indoor air quality are room quality, sociocultural factors, open space relief, environmental capacity, economic factors, and room maintenance. This result is a modified model of the fourth pillar of sustainability, according to Hawkes’ theory on housing planning. The variable human cultural dimensions are knowledge, perception, behaviour, and participation, which frame the sustainable development concept: the social dimension, environmental dimension, and economic dimension.